Tourism Industry Crisis and its Impacts: Investigating the Indonesian Tourism Employees Perspectives’ in the Pandemic of COVID-19 - Riadil, Ikrar Genidal (Politeknik Pariwisata NHI Bandung, 2020)
The recent outbreak of Novel Coronavirus COVID-19 caused a worldwide paranoia due to its fatal nature. The pandemic of COVID-19 affects globally and also in Indonesia itself, wherein Indonesia, one of the affected, is the tourism sector. Indonesia is currently conscious of this pandemic infection, and harms the company, someone’s job career, especially since this pandemic disease is getting worse, it also has an impact on the tourism and hospitality sectors. This study is to investigate the Indonesian tourism employee’s perspectives’ who are working in the realm of tourism and hospitality industry, to see the impact of their jobs career. The researcher will use a qualitative study for this research. The study's data is collected from tourism employees in Indonesia, and ten questions have given to the employees. There are fifty-two tourism employees from a different company in Indonesia have participated in filling the questionnaires. Moreover, results are also generally highlighted in Indonesia about negatively impact the Indonesian to negatively impact the Indonesian tourism and the hospitality industry as a consequence of a significant pandemic of disease spreading throughout the world. Some positive and negative perspectives that are also apparent in the result of questionnaires. The conclusion, the aim of the study will further help the authority to take precautions and relevant policies also to be incorporated in the future. Also, it is to investigate the tourism employees from a different company in Indonesia’s beliefs and perspectives toward the impact of their jobs career in the pandemic COVID-19 have a good impact or not for jobs career.